Determinants and effects of street hawking among teenage girls in gate area of Ibadan (2019)
The study investigated the causes and effect of Street hawking on teenage girls in Gate area, Ibadan. The study adopted the descriptive survey research design while simple random sampling technique was used to select 50 hawkers for the study. The instrument employed was a questionnaire which was tested to be valid and reliable. The research questions were answered using frequency, percentages and mean. The study revealed that the causes of Street hawking among teenage girls in Gate, Ibadan include inadequate family income (Mean = 2.98), unemployment of parents (Mean = 2.52), to support family (Mean = 3.10) and to make money for self (Mean = 2.78). Also, it was found that the effects of Street hawking on teenage girls in gate, Ibadan include the following: 1 sometimes feel unhappy because I am hawking (Mean = 3.04), I have incurred injuries in the course of hawking (Mean = 2.64), I have experienced physical violence while hawking (Mean = 2.82), I have been sexually harassed in the course of hawking (Mean = 2.70) and Some of my colleagues have offered me alcohol to drink while hawking (Mean = 2.66). The study concluded that Street hawking among teenage girls should of importance be stopped. The factors causing Street hawking are to be improved upon so as to prevent the negative consequences of Street hawking among teenage girls. It was therefore, recommended that government should enlighten the general public on the negative effects of Street hawking by teenagers. Also, government should provide programmes that will increase household income of parents